2004
DOI: 10.1046/j.1538-7836.2004.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of the EPCR gene, plasma sEPCR levels and the risk of deep venous thrombosis

Abstract: Summary. Background: Binding of protein C (PC) to the endothelial cell PC receptor (EPCR) stimulates PC activation by increasing the affinity of PC for the thrombin‐thrombomodulin complex. A soluble form of this receptor (sEPCR) circulates in plasma and inhibits both PC activation and APC anticoagulant activity. Objectives: The aim of this study was to investigate whether variations in the EPCR gene or plasma sEPCR levels are risk factors for deep venous thrombosis (DVT). Patients/methods: In a large case‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
188
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(209 citation statements)
references
References 40 publications
11
188
4
2
Order By: Relevance
“…There is no consensus as to whether the presence of the A3 haplotype per se increases the risk of VTE. Three reports indicated that the A3 haplotype is not associated with an increased VTE risk 15,16 and had no effect on the risk of VTE in factor V Leiden carriers, 19 whereas another report showed that the A3 haplotype was associated with a 2.5-fold increased risk of VTE in men but not in women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus as to whether the presence of the A3 haplotype per se increases the risk of VTE. Three reports indicated that the A3 haplotype is not associated with an increased VTE risk 15,16 and had no effect on the risk of VTE in factor V Leiden carriers, 19 whereas another report showed that the A3 haplotype was associated with a 2.5-fold increased risk of VTE in men but not in women.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, its association with risk of VTE is controversial. [14][15][16] sEPCR retains its ability to bind both protein C and activated protein C (APC), and blocks APC anticoagulant activity. 17,18 Haplotype 1 (A1), tagged by the rare allele of 4678G/C, was reported to be associated with increased levels of APC and a reduced risk of VTE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four haplotypes involved in alteration of soluble EPCR levels were demonstrated, among which, the haplotype 3 (H3) is linked with increased soluble EPCR levels. This haplotype is identified by the G/C/A/G combination at positions 1651, 3610, 4216, and 6936, respectively [13]. Moreover, 4678G/C (rs 9574) is a singlenucleotide polymorphisms (SNP) representative of one of the four different haplotypes in the EPCR gene, haplotype 1 (H1) [13].…”
Section: Introductionmentioning
confidence: 99%
“…This haplotype is identified by the G/C/A/G combination at positions 1651, 3610, 4216, and 6936, respectively [13]. Moreover, 4678G/C (rs 9574) is a singlenucleotide polymorphisms (SNP) representative of one of the four different haplotypes in the EPCR gene, haplotype 1 (H1) [13]. Poor pregnancy outcome was associated with specific gene variants and altered soluble EPCR levels in some [14] but not all [15] studies.…”
Section: Introductionmentioning
confidence: 99%